Ethical and Social Dimensions of Citizen Energy Development: The Case of Energy Cooperatives in Poland - Blaszke, Małgorzata (Studia Ecologiae et Bioethicae, 2026)
This article examines the role of energy cooperatives in the process of a just energy transition in Poland, combining descriptive quantitative analysis with normative-ethical reflection. Energy cooperatives are presented not merely as mechanisms for producing renewable energy, but as community-based organisational forms grounded in the values of ecological responsibility, the common good, and socio-environmental solidarity. Drawing on data concerning the number of registered entities, metering points, installations, and installed capacity, the study identifies pronounced regional disparities. The article argues that the development of citizen energy is closely associated with access to resources, the quality of institutional support, and the active engagement of local communities. Energy cooperatives are interpreted as key components of both integral ecology and energy democracy, with the potential to contribute to the co-creation of a fairer and more sustainable energy system. The paper concludes with a set of strategic recommendations aimed at expanding this model in the spirit of equity and shared responsibility.